2015
DOI: 10.15376/biores.10.4.8487-8497
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Organic Compounds in the Ambient Air of a Paper Mill- A Case Study

Abstract: In this work, volatile organic compounds (VOCs) in the ambient air of a secondary fiber paper mill were analyzed. For the sake of studying pollution comprehensively, four sites in the paper mill were analyzed and active sampling methods were used. Desorption was carried out with two solvents, carbon disulfide and dichloromethane. The compositions of VOCs were determined by gas chromatography-mass spectrometry (GC-MS) method. The main identified substances in the four sites were as follows: (1) waste paper sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…It can be noticed that the industrial units of PVC, iron and steel, paper, machinery, gas power, sewage plants, and so forth, are situated north of the suburban site (Figure 1). Several studies have reported that BTEX and acetaldehyde are emitted in significant amounts from PVC, paper mills, coal power plants, landfill, and cement industries (Dave et al., 2020; Evans, 2009; Garcia et al., 1992; Liu et al., 2019; Scott et al., 2020; Tong et al., 2015). In addition, the emission from sewage treatment plants can also be a source of toluene, benzene, xylene, acetone, acetaldehyde and methanol (Byliński et al., 2019; Quigley & Corsi, 1995; Yang et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It can be noticed that the industrial units of PVC, iron and steel, paper, machinery, gas power, sewage plants, and so forth, are situated north of the suburban site (Figure 1). Several studies have reported that BTEX and acetaldehyde are emitted in significant amounts from PVC, paper mills, coal power plants, landfill, and cement industries (Dave et al., 2020; Evans, 2009; Garcia et al., 1992; Liu et al., 2019; Scott et al., 2020; Tong et al., 2015). In addition, the emission from sewage treatment plants can also be a source of toluene, benzene, xylene, acetone, acetaldehyde and methanol (Byliński et al., 2019; Quigley & Corsi, 1995; Yang et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…1 VOCs, such as formaldehyde (HCHO, mainly produced from the alkali recovery outlet) and benzene (C 6 H 6 ), and TRS, such as hydrogen sulfide (H 2 S, mainly released from the black liquor evaporation port), greatly exceed the prescribed emission standards, especially in the air environment of paper mills containing a pulping section. [2][3][4][5] These air contaminants can cause cardiovascular and respiratory diseases or even cancer. 6,7 Several strategies are employed to control the release of air contaminants; particularly, photocatalysis holds promise in decomposing air contaminants adsorbed on the photocatalyst surface into non-toxic CO 2 and H 2 O using oxidizing species (e.g., hydroxyl radicals), which are produced when the photocatalyst absorbs luminous energy exceeding its bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…1 VOCs, such as formaldehyde (HCHO, mainly produced from the alkali recovery outlet) and benzene (C 6 H 6 ), and TRS, such as hydrogen sulfide (H 2 S, mainly released from the black liquor evaporation port), greatly exceed the prescribed emission standards, especially in the air environment of paper mills containing a pulping section. 2–5 These air contaminants can cause cardiovascular and respiratory diseases or even cancer. 6,7…”
Section: Introductionmentioning
confidence: 99%